Analisis Sintaks Desain Evaluasi Pembelajaran Sastra Melalui Model Project Based Learning (PjBL) di UPT SMP Negeri 17 Medan - Safinatul Hasanah Harahap; Ela Emayusnita Sirait; Erfriani Sekar Talenta Simangunsong; Fadilla Aura Ramadani; Kristin Dwi Amsari Pasaribu; Daniel Christian Sinaga; Johannes Bagas Sitorus (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research aims to design syntax in literature learning using the Project Based Learning (PjBL) model at UPT SMP Negeri 17 Medan. This research focuses on the effectiveness of applying PjBL syntax in improving students' literary understanding, critical thinking skills and creativity. This research uses a qualitative descriptive method with data collection techniques through observation, interviews and documentation. Research findings reveal that the application of the PjBL model in literature learning has a positive impact on student engagement and in-depth understanding of literary material. Project-based evaluations also help students develop collaboration and communication skills. Systematic implementation of PjBL syntax provides a clear and effective learning structure, thereby improving the overall quality of learning.